The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/ija.ija_456_17
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid management: From physiology to improving clinical outcomes

Abstract: Perioperative fluid management is a key component in the care of the surgical patient. It is an area that has seen significant changes and developments, however there remains a wide disparity in practice between clinicians. Historically, patients received large volumes of intravenous fluids perioperatively. The concept of goal directed therapy was then introduced, with the early studies showing significant improvements in morbidity and mortality. The current focus is on fluid therapy guided by an individual pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
0
33
1
6
Order By: Relevance
“…This makes norepinephrine a possible choice for elderly patients with relative contraindications of phenylephrine, such as low baseline HR or poor cardiac function. We did not include such patients because of the monitoring indicators-PPV, which was not suitable for patients with arrhythmias [3]. Currently, studies are exploring the optimum single dose for use as a continuous infusion rate during other surgeries in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes norepinephrine a possible choice for elderly patients with relative contraindications of phenylephrine, such as low baseline HR or poor cardiac function. We did not include such patients because of the monitoring indicators-PPV, which was not suitable for patients with arrhythmias [3]. Currently, studies are exploring the optimum single dose for use as a continuous infusion rate during other surgeries in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, prolonged surgery, intraoperative blood loss and volume of crystalloid uid resuscitation increased are harmful to the early rapid recovery of patients [2]. The goals of intraoperative uid management are to maintain central euvolemia and minimize excessive salt and water infusion [3]. Excessive uid loading in elderly patients will disrupt glycocalyx, which is a carbohydrate-rich layer lining the endothelium that plays a crucial role in maintaining endothelial integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Another major component of the ERP is fluid management monitoring, which is known to be associated with less anastomotic complications, less postoperative ileus, less acute urinary retention and reduce hospital stay. It also decreases medical complications such as cardiac insufficiency, respiratory failure or acute kidney injury 25‐27 . Patients with cancer were more likely to benefit from fluid management monitoring but the proportion of patients concerned was less than 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Salmasi et al [38] found that MAP below the absolute value of 65 mmHg or a decrease of >20% of baseline can increase the risk of postoperative myocardial damage. The main goal of perioperative fluid management is optimal microcirculatory perfusion, which can be achieved with well-controlled blood pressure and adequate volume expansion [39]. Some authors suggest that the right amount of fluid can be input during parathyroidectomy, but the absolute amount of liquid should not be fixed [38].…”
Section: Discussionmentioning
confidence: 99%